Transient hypopigmentation in a black preterm newborn managed with Tegaderm®. - De Rose, D.U.; Barone, G.; Aurilia, C.; Frezza, S.; Gallini, F. (European Journal of Pediatric Dermatology, 2018)
The transepidermal water loss is high in the newborn with a very low weight (ELBW) at birth. Recent studies show that the use of Tegaderm® in the ELBW newborn significantly reduces the problems resulting from the loss of water through the epidermis. A hypopigmentation secondary to the use of Tegaderm® was described.